A Synergistic Effect of Serotonin Transporter Gene Polymorphism and Smoking in Association with CHD - Arinami, Tadao; Ohtsuki, Tsuyuka; Yamakawa-Kobayashi, Kimiko; Amemiya, Hiroshi; Fujiwara, Hideomi; Kawata, Ken-ichi; Ishiguro, Hiroki; Hamaguchi, Hideo (Thrombosis and Haemostasis, 1999)
Serotonin induces vasoconstriction in the presence of atherosclerotic lesions. Platelets acquire serotonin from the extracellular space by serotonin transporter and release it following aggregation. There is a functional polymorphism in the serotonin transporter (5-HTT) gene promoter associated with transcriptional efficacy and plasma serotonin levels. To examine whether the polymorphism is associated with coronary heart disease (CHD) in the Japanese, we analyzed 144 male CHD patients with an onset age before 65 and 222 apparently healthy men. The L allele was observed significantly more frequently in the CHD patients (26%) than in the control subjects (19%); the odds ratio was 1.48 (p <0.03). A significant interaction between the polymorphism and smoking was observed for CHD (p = 0.03), suggesting that the two have a synergistic effect on CHD. Odds ratio of the combination of the L allele and smoking was 1.95 (p <0.003). The 5-HTT gene promoter polymorphism may play a role in susceptibility to CHD, particularly when it is combined with smoking.